Ring Recoveries from Steppe Eagles and Eastern Imperial Eagles from the Russian and Kazakhstan Breeding Populations and a Review of Major Threats to Eagles in Iraq - Omar F. Al-Sheikhly; Ali N. Al-Barazangi; Mukhtar K. Haba; Nadheer A. Fazaa; Husham K. Abdulzahra; Mufid Kassim Abou Turab; Ahmad J. Al-Azawi (Пернатые хищники и их охрана, 2018)
The article summarizes ring recoveries from 2 Steppe Eagles (Aquila nipalensis) and 2 Eastern Imperial Eagles (Aquila heliaca) from Iraq that were ringed in Russia and Kazakhstan, as well as ring recoveries from 2 Steppe Eagles and 3 Eastern Imperial Eagles from the border regions of Iraq (Iran, Kuwait and Saudi Arabia) that were ringed in Russia. Threats for eagles in Iraq are discussed in this article.